Methicillin-resistant and methicillin-susceptible Staphylococcus from vervet monkeys (Chlorocebus sabaeus) in Saint Kitts - Hoefer, A.; Boyen, F.; Beierschmitt, A.; Moodley, Arshnee; Roberts, M.C.; Butaye, P. (MDPI, 2021)
Antimicrobial resistance has been described in all ecosystems, including wildlife. Here we investigated the presence of methicillin-resistant and susceptible staphylococci in both colony-born and wild vervet monkeys (Chlorocebus sabaeus). Through selective isolation, PCR, MALDI-TOF, and whole-genome sequencing, methicillin-resistant and susceptible Staphylococcus spp. isolated from vervet monkeys were characterized. We obtained putatively methicillin-resistant staphylococci from 29 of the 34 nasal samples collected. Strains were identified by MALDI-TOF analysis. Staphylococcus cohnii (n = 15) was the most commonly isolated species, while nine other species were isolated one or two times. PCR analysis indicated that eight [28%] strains were mecA positive. The whole-genome sequencing [WGS] included eight methicillin-resistant strains (S. epidermidis (n = 2), S. cohnii (n = 3), S. arlettae (n = 2) and S. hominis (n = 1)), nine additional S. cohnii strains and two strains that could not be identified by MALDI-TOF, but genetically characterized as one S. cohnii and one S. warneri. Different resistance genes carried by different mobile genetic elements, mainly blaZ (n = 10) and tet(K) (n = 5) were found, while msr(A), cat, fosB, dfrG, erm(C), mph(C) and str were identified in one to three strains. Phylogenetic analysis of the S. cohnii strains based on SNPs indicated four clusters associated with colony born or wild. In addition, one singleton S. cohnii isolated did not form a separate group and clustered within other S. cohnii strains submitted to the NCBI. In this study, we demonstrated the presence of AMR and mobile genetic elements to both colony-born and wild vervet monkeys. We also identified a previously undescribed prevalence of S. cohnii in the nasal flora of these monkeys, which merits further investigation.